Analisa Sistem Proteksi Petir Pada Sutt 150 KV Menggunakan Software ATP - Sano, Havel Alindo; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Electrical energy is very important today. The power company distributes the electric energy through the 150 kV overhead lines. The transmission line is a major part of the electrical energy distribution process. Overhead lines are supported by high towers, therefore the overhead lines and towers prone to lightning. The lightning current leads to the increasing voltage on the overhead lines. Surge arrester is a protective device used to protect overhead lines from lightning current. The analysis of the performance of the surge arrester against the lightning impulse requires the investigation in the placement of the surge arrester and the number of surge arresters installed. This study aims todetermine the magnitude of the voltage caused by lightning strikes by varying the location of the surge arrester on the overhead lines. This study was conducted by selecting a lightning strike at apeak voltage of 10 MV on a transmission tower using ATP software. This study indicated that the installation of surge arresters on the overhead lines for each tower leads to droping voltage verywell. The result of study shows that the best result was to install the arresters on each tower phase by decreasing the voltage at 1st tower by 0,4679 MV (92,81%), 2nd tower 0,5674 MV (92,64%), 3rd tower 1,2248 MV (85,79%), 4th tower 10 MV (0%), 5th tower 1,2322 MV (86,09%) and 6th tower 0,6219 MV (92,53%).Keywords : Lightning strikes, surge arrester, peak voltage, placement of surge arrester , voltage drop